2017
DOI: 10.18203/2349-2902.isj20175553
|View full text |Cite
|
Sign up to set email alerts
|

Desarda’s versus Lichtenstein technique of inguinal hernia repair

Abstract: INTRODUCTIONInguinal hernia is one of the most common diseases manage by surgeon.1 A hernia is abnormal protrusion of a viscus or a part of viscus through an opening in the wall of cavity containing it. It tends to occur at natural areas of weakness, where muscles are not strong and are vulnerable to intra-abdominal pressure. The estimated lifetime risk for inguinal hernia is 27% for men and 3% for women. 2The choice of a surgery depends on the surgeon as there were no written surgical guidelines for hernia tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 20 publications
(25 reference statements)
1
9
0
1
Order By: Relevance
“…The rate of wound infection in mesh vs non-mesh technique of inguinal hernia surgery is found 3.4% vs 2.8% in a systematic review of 16 trials 21 . Our results (4.35 vs 1.85%, L and D respectively) are consistent with most of the RCTs published so far [12][13][14][15]20 .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The rate of wound infection in mesh vs non-mesh technique of inguinal hernia surgery is found 3.4% vs 2.8% in a systematic review of 16 trials 21 . Our results (4.35 vs 1.85%, L and D respectively) are consistent with most of the RCTs published so far [12][13][14][15]20 .…”
Section: Discussionsupporting
confidence: 93%
“…EHS guideline concludes that operation technique using mesh results in lower recurrence than technique which do not use mesh but we found no recurrence in our study in either group at 2 years follow up. Many studies show similar results 10,14,15 . However, Desarda, in a clinical trial in small district in India comparing his technique to Lichtenstein repair reported no recurrence in his technique versus 4 recurrences in mesh group 26 .…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations